Non-thyroidal Illness in Children with Congestive Heart Failure - Sahoo, Biswajit; Dabas, Aashima; Goswami, Binita; Agarwal, Anurag; Kurian, Sumod (Journal of clinical research in pediatric endocrinology, 2024)
To estimate the proportion and risk factors of non-thyroidal illness (NTI) in children with congenital heart disease (CHD) with congestive heart failure (CHF). This study enrolled children (6 weeks to 60 months age) with CHD and CHF. The clinical profile and disease severity, derived from the Pediatric Early Warning Score (PEWS) was recorded. Baseline blood samples were taken within 24 hours of hospitalization and evaluated for free tri-iodothyronine (fT3), free thyroxine (fT4), thyroid stimulating hormone (TSH), N-terminal pro-brain natriuretic peptide (NT pro-BNP) and reverse T3. A total of 80 (64 acyanotic CHD) children of median (interquartile range) age 5 (2.5, 8.0) months were enrolled. NTI was seen in 37 (46%) of whom 27 had low fT3 levels. The proportion of NTI was highest in children with severe disease (20/30), than moderate (4/9) or mild disease (13/41) (p=0.018). Ten (27%) patients with NTI died compared to 2 (4.7%) without NTI with unadjusted odds ratio (OR) [95% confidence interval (CI)] 7.593 (1.54, 37.38); p=0.006. After adjusting for NTI, shock and NT-pro-BNP levels, PEWS was the only significant predictor of mortality (OR: 1.41, 95% CI: 1.03, 1.92; p=0.032). Linear regression for fT3 identified a significant relationship with log NT-BNP [beta -3.541, (95% CI: -1.387, -0.388)] and with TSH [beta 2.652 (95% CI: 0.054, 0.383)]. The cutoff (area under the curve, 95% CI) that predicted mortality were fT4 <14.5 pmol/L (0.737, 0.60, 0.88), fT3/rT3 index <1.86 pg/ng (0.284, 0.129, 0.438) and NT pro-BNP >3725 pg/mL (0.702; 0.53, 0.88). NTI was present in a significant proportion of children with CHD and CHF. fT3 level was significantly associated with NTBNP levels and thus severity of CHF.